2003
DOI: 10.1107/s1600536803009401
|View full text |Cite
|
Sign up to set email alerts
|

2-(2-Hydroxyphenyl)-1,3-dithiane

Abstract: Key indicatorsSingle-crystal X-ray study T = 293 K Mean '(C±C) = 0.004 A Ê R factor = 0.063 wR factor = 0.137 Data-to-parameter ratio = 15.2 For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…), and the existence of the X-H • • • S (X ) N, O) HB is well established from the crystallographic data on proteins and organic molecules. [4][5][6][7][8][9][10][11][12][13][14][15] Despite this, the experimental investigations have been very scant on the X-H • • • S hydrogen-bonded systems. A large number of computational studies have been devoted, however, to investigate either the H-S • • • π or S-H • • • π interaction in the case of H 2 S and aromatic hydrocarbon complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), and the existence of the X-H • • • S (X ) N, O) HB is well established from the crystallographic data on proteins and organic molecules. [4][5][6][7][8][9][10][11][12][13][14][15] Despite this, the experimental investigations have been very scant on the X-H • • • S hydrogen-bonded systems. A large number of computational studies have been devoted, however, to investigate either the H-S • • • π or S-H • • • π interaction in the case of H 2 S and aromatic hydrocarbon complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur also happens to be a biologically abundant element (amino acids, disulfide bridges, etc. ), and the existence of the X−H···S (X = N, O) HB is well established from the crystallographic data on proteins and organic molecules. Despite this, the experimental investigations have been very scant on the X−H···S hydrogen-bonded systems. A large number of computational studies have been devoted, however, to investigate either the H−S···π or S−H···π interaction in the case of H 2 S and aromatic hydrocarbon complexes. The authors’ first report on the experimental observation of O−H···S HB in simple model compounds of two naturally occurring amino acids, tyrosine and methionine ( p -CResol was taken for tyrosine and dimethyl sulfide (DMS) for methionine), indicated that the O−H stretch red shift in these systems was almost the same as that for the O−H···O HB in the case of the p -cresol-(H 2 O) 1 complex.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported previously the crystal structure of 1 (WADROJ). 15 In 1, the dithiane ring adopts a chair conformation and the arrangement about the central C-C bond joining the dithiane and phenyl rings is such that one C-S bond lies approximately perpendicular to the plane of the phenyl ring (viewed in projection; see Fig. 2).…”
Section: Crystal Structure Ofmentioning
confidence: 99%